Synthesis, Characterization And Anticancer Studies Of Ne\V Silver(I)-Nheterocyclic Carbene Complexes Derived From Nitrile-Functionalized Imidazolium Salts - Hafiz, Zetty Zuliklia (2014)
Five new nitrile-functionalized N-heterocyclic carbene (NHC) salts namely, 3-(2-cyanobenzyl)-I-methylimidazolium hexafluorophosphate (1.PF6), 3-(3- cyanobenzy1)-l-methylimidazolium hexafl uorophosphate 1,3-bis(2- cyanobenzyl)imidazolium bromide (3.Br), 1,3-bis(2-cyanobenzyl)imidazolium hexafluorophosphate (4.PF6) and 1,3-bis(3-cyanobenzyl)imidazolium hexafluorophosphate (5.PF6) have been successfully synthesized in excellent yield (76-91 %). These imidazolium salts then were treated with a basic metal source, silver oxide, via a simple complexation reaction to afford six novel silver complexes (C1-C6) in good yields (69-84%).